2000
DOI: 10.1016/s0042-6989(99)00235-7
|View full text |Cite
|
Sign up to set email alerts
|

Larger effect of aging on the perception of higher-order stimuli

Abstract: Widespread deficits are known to accompany normal aging. Contrast thresholds of older and younger observers were measured for static and drifting gratings defined by luminance (first-order) or by contrast (second-order), and for a temporally segmented second-order motion stimulus. Results showed that older individuals had a larger threshold elevation for the perception of second-order stimuli than for the perception of first-order stimuli. This suggests a dissociation between the mechanisms underlying the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
123
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 128 publications
(144 citation statements)
references
References 33 publications
16
123
1
4
Order By: Relevance
“…These results suggest that the poor performance in the fine texture case is a result of insensitivity to highfrequency image content in the older adult group. Importantly the known deficiency for texture processing (Habak & Faubert, 2000) transfers into shape judgement tasks: our hypothesis is supported. While it is possible that the slight difference in base contrast between the binary and fine/coarse textures explained the differences in performance for some texture pairings, the effect of such a small contrast change is likely to be very much less than the difference observed here (Schofield & Georgeson, 1999).…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…These results suggest that the poor performance in the fine texture case is a result of insensitivity to highfrequency image content in the older adult group. Importantly the known deficiency for texture processing (Habak & Faubert, 2000) transfers into shape judgement tasks: our hypothesis is supported. While it is possible that the slight difference in base contrast between the binary and fine/coarse textures explained the differences in performance for some texture pairings, the effect of such a small contrast change is likely to be very much less than the difference observed here (Schofield & Georgeson, 1999).…”
Section: Discussionsupporting
confidence: 57%
“…Further, the efficacy of the manipulation employed is known to depend on high-frequency (fine) components in the underlying texture (Sun & Schofield, 2011). Since older adults are known to be less sensitive to such fine detail than young adults (Weale, 1986) and also less sensitive to modulations of texture contrast/amplitude (Habak, 2000) we predicted that they would be less able to distinguish between the corrugations and stripes in our simulations especially when a finegrained texture was used. This prediction was borne out in the data from Experiment 1 which showed that, despite being able to do the task about as well as the younger participants, when binary and relatively coarse grained textures were used, older adults required significantly stronger modulations of texture amplitude when fine-grained textures were used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is possible that aging alters the nervous system in a diffuse way (17), with changes in the mechanisms involved in the processing of spatial frequency and radial frequency stimuli. The available literature suggests that these stimuli (i.e., radial frequency and sine-wave gratings) are most Our results are preliminary and we are still running additional related experiments to better establish the effects of aging on the visual processing of radial frequencies.…”
mentioning
confidence: 99%